2011
DOI: 10.1016/j.pscychresns.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

MAO A VNTR polymorphism and amygdala volume in healthy subjects

Abstract: The X-linked Monoamine Oxidase A (MAO A) gene presents a well known functional polymorphism consisting of a variable number of tandem repeats (VNTR) (long and short variants) previously associated with altered neural function of the amygdala. Using automatic subcortical segmentation (Freesurfer), we investigated whether amygdala volume could be influenced by this genotype. We studied 109 healthy subjects (age range 18-80 years; 59 male and 50 female), 74 carrying the MAO A High-activity allele and 35 the MAO A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…At least one study found that MAOA-L carriers display reduced amygdala volumes bilaterally relative to MAOA-H carriers 15 . By contrast, another investigation reported no difference in amygdala volume by MAO-A genotype 26 . The wide age range (18–80 years) of the second sample compared with the younger age of the participants tested in the first study was suggested as one reason for the discrepant results.…”
Section: Introductionmentioning
confidence: 84%
“…At least one study found that MAOA-L carriers display reduced amygdala volumes bilaterally relative to MAOA-H carriers 15 . By contrast, another investigation reported no difference in amygdala volume by MAO-A genotype 26 . The wide age range (18–80 years) of the second sample compared with the younger age of the participants tested in the first study was suggested as one reason for the discrepant results.…”
Section: Introductionmentioning
confidence: 84%
“…Amygdala activity during emotional face-matching increases with childhood stress in male MAOA-L carriers and decreases with childhood stress in male MAOA-H carriers, with the reverse holding in females (Holz et al, 2016). Amygdala volume, however, was not affected by MAO-A genotype or an interaction effect between genotype and sex (Cerasa et al, 2011). Increased hippocampal activity (Meyer Lin-denberg et al, 2006) and dysregulated vmPFC (Buckholtz et al, 2008) were observed in MAOA-L males but not females (see Figure 1).…”
Section: Potential Pathways Of Sex Modulation Of Genetic Polymorphismsmentioning
confidence: 92%
“…The automated procedures for volumetric measures of several deep GM structures have been previously described (Cerasa et al 2011; Fischl et al 2002). This procedure automatically provided segments and labels for up to 40 unique structures and assigned a neuroanatomical label to each voxel in an MRI volume based on probabilistic information estimated automatically from a manually labeled training set.…”
Section: Methodsmentioning
confidence: 99%